2018
DOI: 10.1136/bmjopen-2018-023188
|View full text |Cite
|
Sign up to set email alerts
|

Association of postlunch napping duration and night-time sleep duration with cognitive impairment in Chinese elderly: a cross-sectional study

Abstract: ObjectiveTo analyse the independent and combined associations of postlunch napping duration and night-time sleep duration with risk of cognitive impairment among Chinese elderly.DesignA cross-sectional study.SettingWe analysed the data from Zhejiang Ageing and Health Cohort, a population-based survey of seven counties located in Zhejiang province in eastern China.Participants10 740 participants aged 60 years or older were included in final analysis.Primary and secondary outcome measuresCognitive impairment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…Lin et al [10] conducted a large-scale cross-sectional study in 10,740 Chinese older adults (≥60 years) and found that short nappers (<30 min) had a signi cantly lower prevalence of cognitive impairment as assessed by the MMSE compared to no nappers and long nappers (≥30 min). Our ndings are consistent with this report.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lin et al [10] conducted a large-scale cross-sectional study in 10,740 Chinese older adults (≥60 years) and found that short nappers (<30 min) had a signi cantly lower prevalence of cognitive impairment as assessed by the MMSE compared to no nappers and long nappers (≥30 min). Our ndings are consistent with this report.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study in clinical settings, Asada et al [21] found that napping for up to 60 min, but not more than 60 min, was protective against the development of Alzheimer's disease. Lin et al [10] conducted a large-scale cross-sectional study in 10,740 Chinese older adults (≥60 years) and found that short nappers (<30 min) had a signi cantly lower prevalence of cognitive impairment as assessed by the MMSE compared to no nappers and long nappers (≥30 min). Our ndings are consistent with this report.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations